Kebijakan Pemerintah dalam Menanggulangi Kekerasan Seksual Anak di Bawah Umur (Studi di Kabupaten Aceh Utara) - Safrida Safrida; Desi Maulida (Universitas Teuku Umar, 2020)
The current problems of globalization era including sexual violence of underaged including rape and abuse, even in North Aceh Regency–child abuse occurs year by year which give negative impact to the future generations thus government need to pay special attention to solve this problem. The purpose of this study is to explain and describe the role of the North Aceh District Government in tackling sexual violence of underaged and to explain and analyze sexual violence which mostly occurs in North Aceh District. Law of Indonesian Republic Number 23 of 2003 concerning child protection. However, for existing law (qanun in Aceh terminology) No. 11/2008 on child protection, sexual violence gets government coordinating with all sectors; providing psychologists in healing trauma and further providing education and guidance of sexual abuse. The obstacles of this research are lack of facilities and lack of commitments in carrying out the rules, lack of religious understanding, lack of deterrent effects provided by government for sexual violence perpetrators thus it is suggested that government provides strict sanctions to the destructive perpetrators nation's generation